A reflexive exploration of two qualitative data coding techniques - Blair, Erik (Journal of methods and measurement in the social sciences, 2015)
In an attempt to help find meaning within qualitative data, researchers commonly start by coding their data. There are a number of coding systems available to researchers and this reflexive account explores my reflections on the use of two such techniques. As part of a larger investigation, two pilot studies were undertaken as a means to examine the relative merits of open coding and template coding for examining transcripts. This article does not describe the research project per se but attempts to step back and offer a reflexive account of the development of data coding tools. Here I reflect upon and evaluate the two data coding techniques that were piloted, and discuss how using appropriate aspects of both led to the development of my final data coding approach. My exploration found there was no clear-cut ‘best’ option but that the data coding techniques needed to be reflexively-aligned to meet the specific needs of my project. This reflection suggests that, when coding qualitative data, researchers should be methodologically thoughtful when they attempt to apply any data coding technique; that they do not assume pre-established tools are aligned to their particular paradigm; and that they consider combining and refining established techniques as a means to define their own specific codes.   DOI:10.2458/azu_jmmss_v6i1_blair